Bowel obstruction following pediatric blunt abdominal trauma: A case series - Alya Barq; Whitman Wiggins; Heather Liebe; Janice A. Taylor; Shawn D. Larson; Steven L. Raymond (Journal of Pediatric Surgery Case Reports)
Introduction: Blunt abdominal trauma is a rare cause of intestinal obstruction. Only case reports and small case series have been described in the literature. Case presentations: Case 1: a 10-year-old female was admitted after a high-speed motor vehicle collision (MVC). She had a seatbelt sign and a grade I splenic laceration. She was discharged one day after the admission. She returned with abdominal pain and nausea twelve days post-trauma and was diagnosed with a small bowel obstruction. She improved spontaneously and was discharged two days later. Two days after the second discharge she presented again with abdominal pain and was taken to the operating room for an exploratory laparoscopy. We found two areas of jejunal narrowing secondary to omental bands. The involved bowel was resected, followed by a primary anastomosis. She recovered uneventfully.Case 2: a 7-year-old male presented after a high-speed MVC. He had a seatbelt sign. A computerized tomography (CT) scan showed mesenteric stranding with small volume pelvic fluid. He was discharged after a four-day hospital stay. He returned forty-two days later with abdominal pain and emesis. A CT scan of the abdomen showed a transition point at the mid-descending colon. He underwent colonic resection of his mid-descending colon due to a stricture. He recovered well post-operatively.Case 3: a 9-year-old male presented to an outside institution following a rear-end high-speed collision. He was discharged shortly after the admission. He returned ten days post-trauma with signs of intestinal obstruction. Abdominal CT showed pelvic fluid and some distended loops of bowel. He was taken to the operating room. We found a stricture in the jejunum. We resected the affected bowel and did an end-to-end anastomosis. He had an uneventful recovery and was discharged on post-operative day three. Conclusion: Blunt abdominal trauma in children can result in intestinal strictures or adhesive bands leading to delayed bowel obstruction. This diagnosis should be considered in children with a recent history of abdominal trauma who develop acute abdominal pain.